Factors Influencing Smoking Habits Among the Students at College of Applied Medical Sciences, Al-Quwayiyah, Shaqra University, Saudi Arabia - Farhan R. Khan (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Smoking is one of the major health problems and its disease complications are increasing day by day. Smoking associated diseases claims life of one in 10 adults globally. By 2030, if this scenario will continue, smoking will kill one in six people. Tobacco smoking is a global epidemic. The World Health Organization has evaluated that tobacco and its concern products kill over 3.5 million people every year. The objective of this research study is to collect a base line data on the tobacco smoking habits of students at College of Applied Medical Sciences, Al-Quwayiyah, Shaqra University, Saudi Arabia. The age range of participating students was 18 to 28 years. An experimental design with common questionnaire, and simple random selection was carried out to 200 students. Out of 200 participants, 51(25.5%) were current smokers. The 18-28 years old age group showed the highest prevalence of smoking. Among the group of the participants most of were cigarette smokers having light smoking habits less than 10 cigarettes per day. They also smoke Moassel and Shisha casually per day. Survey shows that 71% of the current smokers are well aware and had knowledge about disease & hazards of smoking and 74% of them are willing to cease smoking due to its hazards. The conclusion of the research study was that the prevalence of smoking is one quarter among the students of Applied Medical College Sciences, Al-Quwayiyah, Shaqra University. Smoking habits were significantly higher among males (P<0.05) especially those over 19 years of age and whose fathers are smokers.